The Lifelong Learning Scale Through an Indonesian Lens: An Adaptation and Validation Study - Rikumahu, Marchya Carina Exaudy; Murti, Heru Astikasari Setya (Bulletin of Counseling and Psychotherapy, 2025)
This study aims to adapt and validate the Wielkiewicz’s Lifelong Learning Scale (LLS) to ensure its suitability for measuring lifelong learning tendencies among university students in Indonesia. The participants in this study consisted of 808 university students. The adaptation process followed the cultural adaptation guidelines proposed by Beaton et al. (2000), which included forward translation, synthesis, backward translation, expert committee, and test of the pre-final version. Data analysis involved content validity assessment, item discrimination analysis, reliability testing, and confirmatory factor analysis (CFA). The results indicated that Aiken's V values ranged from 0.80 to 0.93, item discrimination indices varied between 0.314 and 0.652, and reliability was α = 0.866. The confirmatory factor analysis yielded χ² = 319, RMSEA = 0.056, SRMR = 0.038, CFI = 0.930, and NFI = 0.905, indicating that the model fit the empirical data. Based on these findings, this measurement instrument is deemed valid and can be used to assess lifelong learning tendencies among university students in Indonesia.